Managing perceived risk for customer retention in e-commerce: The role of switching costs. (8th June 2015) - Yen, Yung-Shen
Abstract : Purpose: – This paper aims to explore how perceived risk affects customer loyalty in e-commerce and how switching costs mediate in the relationship between perceived risk and customer loyalty. Design/methodology/approach: – In this paper, structural equation modeling was conducted, and data on Internet shopping habits of 382 consumers in Taiwan were examined. Findings: – The findings of this study revealed that lowering perceived risks can increase switching costs, which leads to customer loyalty with the service provider in e-commerce. Research limitations/implications: – A sample bias may exist because the sampling was conducted through an online survey in a specific Web site. This study affirmed the theoretical framework regarding the mediation effect of switching costs on perceived risk and customer-loyalty relationships. Practical implications: – To avoid the single effect of reducing perceived risk on customer loyalty, practitioners should be difficult for competitors to imitate. This can increase the barriers to competition, further lock in the customer and can prevent the switch to other service providers. Originality/value: – The findings provide a new feasible approach to customer retention: a business can reduce customers' perceived risk to increase switching costs against the competition for customer retention in e-commerce.